Hypertension and angiotensin system inhibitors in patients with metastatic renal cell carcinoma - Lisa Derosa; Hassane Izzedine; Laurence Albiges; Bernard Escudier (Frontiers Media S.A., 2016)
Arterial hypertension (HTN) is a class effect of anti-vascular endothelial growth factor (VEGF) therapies, including the monoclonal antibody bevacizumab. Data are conflicting regarding the role of the renin-angiotensin system on angiogenesis and recent data suggest that the use of angiotensin system inhibitors (ASIs; angiotensin receptor blockers or angiotensin-converting enzyme inhibitors) is associated with improved survival in metastatic renal cell carcinoma (mRCC), particularly when used with VEGF targeted therapies. The aim of this review is to discuss the available treatment options for mRCC and associated incidence of hypertension as well as summarize the known data about ASIs use and mRCC. Additionally, given that the optimal management of HTN remains unclear, we will focus on prevention strategies and propose potential therapeutic approaches.